Lithium Treatment of a Bipolar Patient with Wilson’s Disease: A Case Report - Rybakowski, J. K.; Litwin, T.; Chlopocka-Wozniak, M.; Czlonkowska, A. (Pharmacopsychiatry, 2013)
We present the case of a male patient with a family history of both bipolar disorder (BD) and Wilson’s disease (WD). Wilson’s disease was diagnosed for this patient in 2008, at the age of 28 years, and shortly thereafter his bipolar illness began with depressive episodes. The patient has been treated with zinc sulphate for WD and with antidepressants for depression. In 2009, lithium was added, and in 2010 antidepressants were discontinued. During treatment with zinc sulphate, a gradual improvement of hepatic indices and a decrease of mandibulofacial dystonia was noted. In 2011, a hypomanic state occurred which subsided with an increase of the lithium dose. Since then, the patient has been mostly in a euthymic mood with subclinical hypomanic periods. We suggest that lithium may be a viable option for treating bipolar illness in patients with Wilson’s disease.
Keywords: bipolar disorder; liver disease patients; lithium